Teacher Evaluation and Academic Demand: Bad Practices in Higher Education - Alderete Güere, Ernesto Gustavo (2020)
Objective. To characterize the predominant attitude in university students of Huancayo on the evaluation of teaching performance. Methods. Research was descriptive substantive type with a mixed approach. An attitude scale towards teacher’s evaluation was made and validated. It was applied to 382 students from Universidad Continental, Universidad Peruana Los Andes and Universidad Nacional del Centro del Perú. In addition, qualitative collection of information, in-depth interviews were conducted with 24 teachers from the three universities. Results. According to the data obtained, the majority of the students consider that teacher evaluation is not valued (79.6%), that it does not have specific objectives (80%), and that they favor "very nice" teachers (54, 3 %). However, they refer that they learn more from a “demanding teacher” than from a “very nice teacher” (56.6%). Teachers, for their part, agree with the evaluation of their performance, but consider that it does not favor the improvement of teaching-learning and they perceive it as an instrument of control and warning on the part of the students. Conclusion. Students and teachers do not value the evaluation of teacher performance because they perceive that it is carried out without specific strategies and purposes.